HDEO
EU
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
Isis575
May 24, 2018, 9:56:50 PM
34
solve y=3x+4 and y=-2x-6 using substitution method
+3
(
1
) Answers
colombianbryan
May 24, 2018, 11:48:41 PM
3x + 4 = -2x - 6 5x = -6 - 4 x = -2 y = (3*-2) + 4 y = -6 + 4 y = -2
Add answer
Sign in
Sign up
Related Questions
solve y=3x+4 and y=-2x-6 using substitution method
Solve using system of equations using the substitution method. 2x+3y=-4 2x-y=7
1/3x+y=9, -2x+2y= -6... what is x and y, using the substitution method?
Solve by Substitution: 3x - y = 4 y = 6 - 2x
How to solve this using substitution. Y=3x and x+y=4
Solve using system using the substitution method X+2y=10 y=4x-4
Solve each system using substitution. 3x+2y=23 1/2x-4=y
Solve the system by using substitution. -2x+5y=19 3x-4=y
Substitution method- y=-x+4 and y=3x
3x+y=-7 -2x+4y=0 Solve by using substitution